Serum reference value of two potential doping candidates-myostatin and insulin-like growth factor-I in the healthy young male - Der-Sheng Han; Chi-Huang Huang; Ssu-Yuan Chen; Wei-Shiung Yang (Taylor & Francis Group, 2017)
Background Myostatin negatively regulates muscle growth, and its inhibition by suitable proteins can increase muscle bulk and exercise performance. However, the reference values of serum myostatin in athletes performing strength training are still lacking. Methods A cross-sectional study recruiting28 male collegiate athletes performing strength training and 29 age-matched normal controls was conducted. The serum concentration of myostatin and insulin-like growth factor 1 (IGF-1), grip strength, and body composition were the main outcome measures. We used regression models to analyze the correlation between serum markers and the physiological parameters. The athlete group had greater height, weight, body mass index (BMI), fat mass percentage, fat-free mass, muscle mass, waist girth, grip strength, and estimated daily energy expenditure. Results The IGF-1 concentration was higher in the athlete group (324 ± 80 vs. 263 ± 134 ng/ml), but the myostatin levels did not differ (12.1 ± 3.7 vs. 12.4 ± 3.5 ng/ml). The reference value for IGF-1 among the healthy young males was 293 ± 114 ng/ml, correlated with age and height; the value for myostatin was 12.3 ± 3.6 ng/ml, correlated negatively with BMI, fat mass percentage, and waist girth after adjustment for age. Conclusion Myostatin level is negatively related to fat percentage, and serum IGF-1 is positively related to height. The reference values could provide a basis for future doping-related study.